The Influence of Servant Leadership, Work Environment, Work Discipline, and Compensation on Employee Job Satisfaction - Rofifah Khoirunnisa; Ignatius Soni Kurniawan; Mohammad Ahyar Syafwan Lysander (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2025)
Employee job satisfaction is an important concern in efforts to improve performance quality and public services. The continued presence of indications of declining employee motivation and engagement highlights the need to address factors influencing job satisfaction. This research investigates how servant leadership, workplace conditions, work discipline, and remuneration impact employee job satisfaction levels. The study adopts a quantitative methodology, targeting the entire workforce of the Depok Sub-District Office as the study population. A complete enumeration sampling approach was applied, involving 36 participants. Data gathering was accomplished through questionnaire administration, while data evaluation employed classical assumption testing and multiple linear regression analysis. The findings reveal that servant leadership, workplace environment, work discipline, and compensation demonstrate positive and statistically significant influences on employee satisfaction. These findings imply that strengthening internal organizational factors, such as leadership, working conditions, discipline, and compensation systems, can be an effective strategy for improving employee satisfaction and productivity in the public sector.